Efeito adjuvante da Propionibacterium acnes sobre células-tronco mesenquimais murinas - Silveira, Gabriela da Paz [UNIFESP] (2016)
Introduction: The adjuvant effect of heat-killed P. acnes and its purified soluble polysaccharide phenol-extracted from bacteria cell wall (PS) had been widely demonstrated. Both are able to modulate different cell populations, such as enhancing hematopoietic stem cells (HSC) from bone marrow (BM). Mesenchymal stem cells (MSC) are an important component of the HSC niche and can regulate HSC function through a complex paracrine signaling network. Because of this, and knowing the importance of MSC for regenerative medicine, our hypothesis turned out to be that these adjuvants could play a role on the murine MSC. Objective: Evaluate the adjuvant effect of heat-killed P. acnes and its PS on murine MSC proliferation and immunomodulation ability. Methods: C57Bl/6j mice were injected subcutaneously once a week with 140 ?g of heat-killed P. acnes suspension or 25 ?g of soluble PS or saline for 3 weeks. Subpopulation of MSC were freshly sorted from bone marrow (BM) using cell markers CD3, CD11b, CD11c, CD19, CD34, CD73, CD90 and CD105. Proliferation rates of BM-MSC were measured by CFSE dilution after 3, 6 and 9 days. MSC and its subpopulations were transplanted in a traumatic brain injury model (TBI) and IL-6, TNF-?, TGF-?, IL-4 e IL-10 expression were analyzed at injury site after 24 h and 7 days post-injury by qPCR. Immunohistochemistry was performed in brain sections in order to quantify neural stem cells (GFAP+BrdU+) and neuroblasts (DCX+BrDU+). Moreover, MSC from Toll-like Receptor 2 Knockout mice (KO TLR2) treated with P. acnes were injected in a C57Bl/6j TBI model. Results: MSC obtained from treated animals were able improve the proliferative capacity when compared to control group. Treatment with P. acnes significantly enhanced MSC modulatory effect by increasing IL-4 expression and attenuating IL6 and TNF-? expression at the acute phase. PS-MSC enhanced IL-4 and IL-10 at acute phase and, after 7 days, enhanced TGF-?. Increment of neural stem cells and neuroblasts were detected in the subventricular zone in response to transplantation of MSC-PS. Injection of freshly sorted MSC subpopulation resulted in similar effect of MSC obtained from culture. They were also able to diminish IL6 and TNF-? expression. PS-MSC-CD90+ elevated IL-4 expression and PS-MSC-CD105+ elevated IL-4 and IL-10 expression, while P. acnes-MSC-CD90 and P. acnes-MSC-CD73 enhanced IL-10 and TGF-? expression respectively at injury site after 24h. P. acnes-MSC-KOTLR-2 transplant revealed a decreasing in anti-inflammatories cytokines in acute phase such as TGF-? and IL-10 when compared with MSC from control or wild-type P. acnes groups. Conclusion: P. acnes as well as its PS compound are an important alternative to increment MSC culture with high immunomodulatory profile. Moreover, adjuvant treatment helped to determine MSC subpopulation responsible for the inflammation resolution. Besides we could show that TLR2 mediated some of these effects induced by P. acnes on MSC.